Capillary electrophoresis for rapid identification of monoclonal antibodies for routine application in hospital. Issue 17 (29th June 2015) - Jaccoulet, Emmanuel; Smadja, Claire; Prognon, Patrice; Taverna, Myriam
<x xml:space="preserve">Abstract</x> mAbs are widely used in cancer therapy. Their compounding, performed just before their administration to patients, is executed in a production unit of the hospital. Identification of these drugs, individually prepared in bags for infusion before patient administration, is of paramount importance to detect potential mistakes during compounding stage. A fast and reliable analytical method based on CZE combined to a cationic capillary coating (hexadimethrine bromide) was developed for identification of the most widely used compounded therapeutic for cancer therapy (bevacizumab, cetuximab, rituximab, and trastuzumab). Considering the high structural and physico‐chemical similarities of these mAbs, an extensive optimization of the BGE composition has been performed. The addition of perchlorate ions and polysorbate in the BGE greatly increased the resolution. To validate the method, an internal standard was used and the relative migration times (RTm) were estimated. Very satisfactory RSDs of the RTm for rituximab (0.76%), cetuximab (0.46%), bevacizumab (0.31%), and trastuzumab (0.60%) were obtained. The intraday and interday RSD of the method were less than 0.32 and 1.3%, respectively for RTm. Significant differences between theses RTms have been demonstrated allowing mAbs identification. Finally, accurate mAbs identification has been demonstrated by a blind test.